Turkey Public Finance Review : Turkey in Transition--Time for a Fiscal Policy Pivot? - World Bank (Washington, DC, 2014)
Turkey has experienced rapid growth and improved social outcomes over the past decade. Per-capita income in United States dollar (USD) terms tripled during the first decade of the 21th century, and Turkey is now the world's 17th largest economy. Fiscal policy was an important component of the reform program that delivered these successes. Prudent fiscal policy also provided the fiscal space to soften the blow of the global economic and financial crisis in 2008-2009. This report documents the central role played by fiscal policy over the last decade and presents simulation results from a computable general equilibrium model that will help inform the future direction of fiscal policy to support sustained high growth. The dynamics of fiscal outcomes and private investment and savings raise a series of tradeoffs for policy going forward. The analysis in this report suggests that public investment can crowd-in private investment and promote a more sustainable growth path. Government revenue dynamics present another set of trade-offs. These fiscal trade-offs are likely to be exacerbated as the structural transformation of Turkey's economy slows down. Structural reforms can support the fiscal policy pivot, particularly by strengthening the supply side of the economy, for instance through an increase in female labor force participation.